Augmentation of autophagy by mTOR-inhibition in myocardial infarction: when size matters - Buß, Sebastian Johannes; Riffel, Johannes; Katus, Hugo; Hardt, Stefan (Autophagy, 2010)
The extent of adverse myocardial remodeling contributes essentially to the prognosis after myocardial infarction (MI). Currently, therapeutic strategies that inhibit remodeling are limited to inhibition of neurohumoral activation. mTOR-dependent signaling mechanisms are centrally involved in the myocardial remodeling process. There exists a controversy as to whether autophagy is beneficial in the setting of myocardial infarction. We now provide evidence that induction of autophagy by inhibition of mTOR with everolimus (RAD) prevents adverse left ventricular remodeling and limits infarct size following myocardial infarction. mTOR inhibition increases autophagy and concomitantly decreases proteasome activity especially in the border zone of the infarcted myocardium. The induction of autophagy via mTOR inhibition is a novel potential therapeutic approach to limit infarct size and to attenuate adverse left ventricular remodeling following MI.